"Google is not fun": an investigation of how Swedish teenagers frame online searching. Issue 6 (4th October 2017) - Andersson, Cecilia
Abstract : Purpose: The purpose of this paper is to investigate the role of Google in everyday online searching activities of Swedish teenagers in different contexts. Design/methodology/approach: The study is qualitative and material has been produced through interviews and observations in two different schools with participants aged 15-16. Goffman's frame analysis provides the analytical lens for studying how activities are assigned meaning. Findings: Three different framings in relation to using Google and googling are identified in the material: Google and fact-finding, Google as a neutral infrastructure, and Google as an authority. There is an interplay between activity, context, and interaction in defining the role of Google. In relation to school, the fact-finding framing is more pronounced whereas the infrastructure framing comes forth more in their free time activities. The authority framing cuts across both framings and underpins their trust in the search engine. Originality/value: The study addresses the way that Google is embedded in online activities and how the search engine is viewed in various contexts, as well as how it is made invisible in some contexts. Previous research has not addressed Google's role in specific in relation to various everyday uses.